Facebook addiction: its relation with academic performance of University students - Tufaila, Muhammad Waseem; Kazmi, Ammar; Muhammad Saleem, Muhammad Saleem; Khan, Rahmattullah (School of Social Sciences, 2015)
The present study intended to find Facebook addiction and its relation with academic performance of university students from Pakistan. Sample comprised of eighty students (n=80) in total whom are purposefully selected and equally divided according to gender. The universe was public sector higher learning institute named as The Islamia University of Bahawalpur, Pakistan. Cross-sectional survey research design was employed. Data were collected by use of Bergen Facebook addition scale. Data were analyzed from SPSS (21.0), descriptive statistics, correlation and regression analysis were computed to test the hypotheses. Results depict significant negative relationship between Facebook addiction and academic performance of students (β = -.907, t = -4.554). Conclusively, female students consume more time to use Facebook as compare to male students; hence, male students exhibit better academic performance. Limitations and future implications of current study were enclosed.